Study of the catalytic activity of bovine bone powder impregnated with Fe(III) new material for the catalytic degradation of Indigo Carmine - Coelho, Márcio Guimarães; de Lima, Geraldo Magela; Augusti, Rodinei; Ardisson, José Domingos; de Andrade, Fabrício Vieira; Duarte, Luciana dos Santos (Eclética Química, 2015)
In this work, a composite consisting of bovine bone powder impregnated with Fe(III) ions was prepared and its performance evaluated as a catalyst for the degradation of the textile dye Indigo Carmine in aqueous medium. One of the advantageous features of this new material is that it is inexpensive, simple to prepare and the support, bovine bone, is one the final residue of food production. The material was fully characterized by X-ray powder diffraction (DRX), 57Fe-Mössbauer spectroscopy, surface area measurements (BET), atomic absorption spectrometry. The degradation of Indigo Carmine was monitored by ultraviolet spectroscopy in the visible region (UV-Vis) and the by-products characterized by direct infusion ESI(-)MS (electrospray ionization mass spectrometry in the negative ion mode).